2018
DOI: 10.1111/crj.12753
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐linked difference in blood oxygen saturation

Abstract: Healthy young female adults have a higher (1.5%) SpO than their male counterparts. This difference is not yet present at birth. Further studies are needed to determine the timing of sex-differences, and to better define the mechanism(s) behind this observation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 24 publications
0
16
2
Order By: Relevance
“…Additionally, physiological parameters such as the peripheral capillary oxygen saturation (SpO 2 ) also seem to succumb these sex-specific influences as Ricart et al [61] measured at sea level slightly but significantly higher SpO 2 values in women than in men. Levental et al [62] confirmed these findings and additionally found no such sex differences in newborns. Thus, the authors assumed that age-related hormonal differences are involved and attributed a possible indirect effect of sex on SpO 2 to the influence of reduced dead space due to women's smaller airways.…”
Section: Differential Neurohumoral Response Pattern and Psychologicalmentioning
confidence: 81%
“…Additionally, physiological parameters such as the peripheral capillary oxygen saturation (SpO 2 ) also seem to succumb these sex-specific influences as Ricart et al [61] measured at sea level slightly but significantly higher SpO 2 values in women than in men. Levental et al [62] confirmed these findings and additionally found no such sex differences in newborns. Thus, the authors assumed that age-related hormonal differences are involved and attributed a possible indirect effect of sex on SpO 2 to the influence of reduced dead space due to women's smaller airways.…”
Section: Differential Neurohumoral Response Pattern and Psychologicalmentioning
confidence: 81%
“…A further explanation may be related to potentially lower hemoglobin levels in the females. Low hemoglobin is associated with an increased level of 2,3-diphosphoglycerate (DPG), due to the decrease in oxygen carrying capacity ( 79 ). This results in a shift in oxyhemoglobin dissociation curve to the right, decreasing the affinity of oxygen to the hemoglobin, and reducing the SpO 2 ( 79 ).…”
Section: Discussionmentioning
confidence: 99%
“…Low hemoglobin is associated with an increased level of 2,3-diphosphoglycerate (DPG), due to the decrease in oxygen carrying capacity ( 79 ). This results in a shift in oxyhemoglobin dissociation curve to the right, decreasing the affinity of oxygen to the hemoglobin, and reducing the SpO 2 ( 79 ). This shift is exaggerated at high altitude and females may be more sensitive to this shift, irrespective of VO 2 max.…”
Section: Discussionmentioning
confidence: 99%
“…However, very few related studies have been conducted on women [37]. Numerous studies investigating sex difference in blood oxygen saturation reported that females have higher average of SpO 2 than males [38] due to sex-specific differences in hormones [39], which regulate breathing control and indirectly induce changes in function of the respiratory system [37,38]. Moreover, it has been acknowledged that estrogen has beneficial effects on CBF [39] as increasing estrogen levels can reduce cerebrovascular resistance [40] and proliferate CBF velocity [41].…”
Section: Introductionmentioning
confidence: 99%